Understanding Family Migration in Rural South Africa: Exploring Children's Inclusion in the Destination Households of Migrant Parents. Issue 4 (8th January 2014) - Bennett, Rachel; Hosegood, Victoria; Newell, Marie‐Louise; McGrath, Nuala
Abstract Despite the removal of restrictions on movement and increasing female participation in migration, only a minority of migrant parents in South Africa include their children in their destination household. Quantitative analyses of the circumstances in which children accompany a migrant parent have been limited by the lack of available data that document family arrangements from the perspective of more than one household. This paper uses data about members of rural households in a demographic surveillance population in KwaZulu‐Natal and a linked sample survey of adult migrants to examine factors associated with children's inclusion in the destination household of migrant parents, analyse the timing and sequence of children's moves to parental destination households, and describe the composition of parental origin and destination households. The findings confirm that in contemporary South Africa, only a small percentage (14%) of migrants' children who are members of the parental origin household are also members of the parental destination household. Membership of the parental destination household is associated with parental characteristics and the child's age, but not measures of socio‐economic status, and children most commonly migrate several years after their migrant parent. Children included in the destination household of migrant fathers frequently live in small households, which also include their mother, whereas children included in the destination household of migrant mothers live in larger households. This study contributes to understanding the contexts of children's inclusion in parental destination households in South Africa and demonstrates the potential of data collected in migrants' origin and destination households. © 2014 The Authors. Population, Space and Place published by John Wiley & Sons Ltd